SELF-EFFICACY, PROFESSIONAL DEVELOPMENT AND WELL-BEING FOR EMPLOYEES IN THE LABOR MARKET - Dreifelde, Ilze; Zakrizevska Belogrudova, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the research of the work environment and employment both in the world and in Latvia, the importance of employees' self-efficacy in work productivity,  professional development and well-being has being actualized. The purpose of this study is to investigate whether there is a correlation  between self-efficacy, professional development and well-being of employees in the labor market in Latvia. Hypothesis: is there a correlation between self-efficacy, professional development and well-being for employees in Latvia. The researchquestion of the study is whether there are statistically significant differences in self-efficacy by gender. The study involved n-224 employees in the Latvian labor market aged 18 to 56, with different levels of professional development and well-being. Three methods were used: General self-efficacy scale, the Survay of self-efficacy in the main activity,Professional development needs survey. The results of the study show that there is a statistically significant relationship between self-efficacy, professional development and well-being of employees in the labor market, as well as it was found that there are no statistically significant differences of self-efficacy by gender.